Comparative Analysis of Wireshark and Windump Software in Network Security Monitoring - Julias Sulicdio; Toibah Umi Kalsum; Yode Arliando (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
Computer security is an important factor in the world of information technology. Computer network security is currently starting to be in great demand by many people. If viewed from the negative side, there will be more types of intrusion or attacks that can be carried out in a network. The aim of this research is the need for network security monitoring to find out disturbances or threats that occur in a network to minimize intrusion. And the results obtained from this research are wireshark and windump software is able to monitoring attacks on a network and software that is able to analyze in more detail is wireshark while windump for further analysis requires experts to get better results.